STRATEGI PERUNDINGAN TIMOR LESTE DENGAN INDONESIA DI BLOK GREATER SUNRISE TAHUN 2004-2010 - Ariwangsa Putra, Dewa Bagus; Dharmiasih, D.A.Wiwik; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
ABSTRAK This research explained Timor Leste’s strategy on hoisting Batek Island ownership issue which is used to gain advantages in negotiation of southern sea border, which is Block Greaater Sunrsie. Qualitative method was used as a means to collect secondary data through the documentation and literature study. Aftewards, all of the secondary data was analysed by using foreign policy theory, concept of national interest and also concept of power to explain the reson behind Timor Leste’s hoisting the ownership issue of Batek Island issue based on intentions to gain one of natural source of power, which is natural resources. By getting that power sources, that’s closely related to the national interest of Timor Leste, that is to pursuit their state survival. That source of power is the means for Timor Leste to achieve of one its national interests, that is state survival.  which is closely related to the national interest of Timor Leste, is one of the main Keywords : national interest , state survival , border dispute , power